Behavior Love Land Water Through Education Citizenship in Elementary School - Fadilah, Ummi (International Journal of Students Education, 2025)
The younger generation or next generation is the generation that will continue the results of the struggles of their predecessors by becoming leaders, who are expected to be able to change and advance this nation to become more prosperous and successful. To create a generation young can become leader which good like which in expect no will happens if a feeling of love and defense of the country does not grow in their hearts and souls. A sense of love for the homeland is very important and must be instilled in the nation’s future young generation, so that in the future nation this can become nation which big and succeed. For it requires a solution to minimize it. A strategic solution to overcome this problem is to implement civic education learning in elementary schools. The purpose of this study is to implement a behavior of love for the homeland through civic education learning in elementary schools. In this case, civic education learning in elementary school is important for held because will forming attitudes which characterful for students. Meanwhile, this study uses a qualitative method by conducting a literature study on the opinions of figures and reviewing journals related to the material. The conclusion of this study is that civic education in elementary schools makes participant educate become inhabitant country who loves his country because in the learning material taught contains character education values, one of which is love for the homeland.